The Effect of Social Media Marketing on Purchasing Decisions of E-commerce Products Through the Role of Brand Awareness in Gen Z Users - Hifa Labiba Afi Huwaida; Edwin Zusrony; Robby Andika Kusumajaya (JURNAL ILMIAH EDUNOMIKA, 2025)
The use of social media enables instantaneous communication and interaction between brands and consumers. This research employs a quantitative approach. The study aims to analyse the effects of social media marketing and brand awareness on the purchase decision of Generation Z towards e-commerce products. A total of 90 respondents belonging to Generation Z and residing in Semarang Regency were selected for the study through purposive sampling. The data was collected using a questionnaire constructed with Likert scale parameters. The SEM-PLS approach was utilised for data analysis, using SmartPLS version 4.1.1.2 for data processing. The SEM-PLS approach comprises two stages: evaluating the outer model and the inner model. The findings of the research confirmed that social media marketing and brand awareness positively impact purchasing decisions. The brand awareness variable does not appear to mitigate the impact of social media marketing on purchasing decisions. It is recommended that e-commerce companies pay better attention to social media marketing strategies and brand awareness to remain competitive in the industry.